Sugar Apple Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Ian Maguire (EDIS, 2006)
Revised! HS-38, a 9-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Ian Maguire, provides homeowners with a greatly expanded basic reference for growing sugar apple in the home landscape. Additional tables include information on selected cultivars for Florida, cultural practices by month, fertilizer program, flowering behavior, and nutritional values. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005.